PENGARUH PENGGUNAAN PRE-EMPTIVE SELF DEFENSE IN WAR YANG DIGUNAKAN OLEH NEGARA YANG SEDANG BERKONFLIK UNTUK PENGECULIAN DALAM TANGGUNG JAWAB HUKUM INTERNASIONAL (Studi Kasus : Pasukan Türkiye Menyerang Kaum Khurdis) - Nathaniel Adianta Rim Manurung; Maria Maya Lestari; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Self-defense is the right of self-defense granted by the UN Security Councilcontained in Article 51 of the UN Charter. This right can be used by a state inorder to defend itself from an attack from another country. It is well known thatthe development of theories about state self-defense rights has overridden theconcepts of anticipatory self-defense and pre-emtive self-defense that override theprovisions requiring armed attacks before state self-defense rights arise. Article51 of the UN Charter clearly states that the right to self-defense of UN memberstates, individually as well as collectively, only arises "if an armed attack occurs".Thus a new state can exercise its martial rights if it has happened or is happening.Normative Legal Research Methods use normative juridical approachmethods. The normative approach in juridical is an approach that refers to theapplicable laws and regulations. Furthermore, normative legal research is a typeof legal research methodology that bases its analysis on applicable laws andregulations and is relevant to the legal issues that are the focus of the research.Topics of legal issues that are relevant to be researched using Normative LegalResearch Methods, including regarding; Intentarization of positive law, legalprinciples, etc.The results of the research that have been obtained prove that first ; there isa lot of neglect of the use of this principle by many countries which has resulted inmany violations that have been committed by the State. Meanwhile, the originalpurpose of making this principle according to the provisions of Article 51 of theUN charter was to protect the entity of a state against threats that would arisefrom outside that resulted in destruction and danger within the state itself.Keywords : State Accountability - Armed conflict - Preemtive of State Self-Defense